2016
DOI: 10.1186/s13256-016-0863-1
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a primary gastric plasmacytoma mimicking intractable gastric ulcer by using high-dose dexamethasone therapy: a case report

Abstract: BackgroundExtramedullary plasmacytoma is a plasma cell neoplasm that presents as a solitary lesion in soft tissue. Most extramedullary plasmacytomas involve the nasopharynx or upper respiratory tract. Primary plasmacytoma of the stomach is extremely rare.Case presentationA 78-year-old Korean woman presented with epigastric pain for 3 months. She had a history of an intractable gastric ulcer despite repeated endoscopic biopsies and appropriate medical therapy for the ulcer. She underwent another endoscopy and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[ 19 ] There is a report which showed that a high-dose dexamethasone (40 mg daily for 4 days every 3 weeks) treatment had an effect on ulcer type gastric EMP. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] There is a report which showed that a high-dose dexamethasone (40 mg daily for 4 days every 3 weeks) treatment had an effect on ulcer type gastric EMP. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%